Hydrocarbon based stabilisers for the synthesis of cross-linked poly(2-hydroxyethyl methacrylate) particles in supercritical carbon dioxide. Issue 42 (11th October 2019) - Parilti, Rahmet; Castañon, Alba; Lansalot, Muriel; D'Agosto, Franck; Jérôme, Christine; Howdle, Steven M.
Abstract : Novel polymeric stabilisers were designed for the development of an environmentally-friendly process to prepare well-defined cross-linked particles of poly(2-hydroxyethylmethacrylate) (PHEMA). Abstract : An environmentally-friendly process to prepare well-defined cross-linked particles of poly(2-hydroxyethyl methacrylate) (PHEMA) was investigated. The dispersion polymerisation of 2-hydroxyethyl methacrylate (HEMA) with a cross-linker ethylene glycol dimethacrylate (EGDMA) was performed in supercritical carbon dioxide (scCO2 ). Stabilisers based only on vinyl acetate (VAc) and vinyl pivalate (VPi) random copolymers P(VAc- stat -VPi) were employed thus avoiding the use of silicone or fluorine based stabilisers which are normally required in scCO2 . The effect of molecular weight and composition of the P(VAc- stat -VPi) stabilisers on the size and shape of the produced microparticles was investigated. A copolymer stabiliser with 56 : 44 (VAc : VPi) molar composition ( M n = 12.8 kg mol −1 ) was found to be the most efficient, resulting in well-defined spherical cross-linked PHEMA particles with a diameter of 1.2 μm. This particular stabiliser was found to provide good steric stabilisation for a range of cross-linker ratios and the addition of a co-monomer such as N -vinylpyrrolidone (NVP) allowed tuning of the properties of the microparticulate products. Finally, the stabiliser plays a second very important role. Partial hydrolysis of the ester groups of the stabiliser located on the surface of the microparticles leads to a hydrophilic surface with alcohol moieties and hence facilitates dispersion of the microparticles into water leading to valuable microgels.